Model Teams Game Tournament Bermediakan Permainan Monopoli Untuk Meningkatkan Kemampuan Membaca Aksara Jawa Siswa Sekolah Dasar - Much Arsyad Fardani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to find out how much the ability to read Javanese script has increased by applying the Teams Game Tournament model with the help of monopoly game media in class IV SD Unggulan Muslimat Kudus. The research method used is classroom action research (CAR). Data collection techniques in this study are observation, tests, questionnaires, and interviews. Data analysis stage with data reduction, data presentation, and conclusion. The results of the study stated that applying the Teams Game Tournament method with the help of monopoly game media had a significant increase. With the acquisition of an average score at the pre-cycle stage of 16.67% with the scores of students who completed only 6 students and 30 students who did not complete, the stage of cycle I was 86.11% with the scores of students who completed 31 students and 5 students who did not complete, as well as in the second cycle stage of 88.89% with the acquisition of 32 students who completed and 4 students who did not complete. Based on these results it can be concluded that there is an influence on the ability to read Javanese script in fourth grade students at Unggulan Muslimat Kudus Elementary School by using the TGT model with monopoly games as media.